AL HALAJ SUFI MATI DALAM TIANG SALIB ( KAJIAN FILSAFAT BEBAS NILAI) - Taufiq . (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
Basically  every  man  according  to  his  nature  acknowledge  their  authority  beyond  himself  who created the universe and its contents, which is called God. Humans tried to describe the presence of  God  in  his  life  according  to  the  ability  of  thought,  there  is  the  God  described  in  the  form  of sculpture, there is described a God, formless, intangible.  In search of the God of the philosophers use a variety of methods, some use the method of Plato, Socrates,  Al-Ghazali  and  so  on.  The  philosophers  have  already  reached  the  level  of  approach  to God,  such  as  Al-Halaj.  Al-Halaj  other  philosophers  as  value-free,  Al-Halaj  a  solid  figure  in  the founding philosophers, so that he died in the gallow